Regional Variations in Myiasis Management Across North Africa: A Systematic Review - Alrouwab, Osamah; Youssef Al-Jatlawi; Issa Amara (AlQalam Journal of Medical and Applied Sciences, 2025)
Myiasis, the invasion of tissues by fly larvae, is a considerable but overlooked public health concern, especially in tropical and subtropical areas. The frequency of myiasis in North Africa is affected by geographic, climatic, and socioeconomic variables; yet, there is a paucity of comprehensive information about its treatment across the area. Regional disparities in healthcare infrastructure, cultural customs, and interruptions due to war exacerbate the challenges in addressing this neglected tropical disease (NTD). The goal of this systematic review is to look at differences in how myiasis is treated in different parts of North Africa, focusing on things like epidemiology, preventative measures, diagnostic methods, treatment options, and the healthcare system. The study finds deficiencies in the literature and offers pragmatic suggestions for governments, healthcare practitioners, and academics. A systematic search was performed across various databases, including PubMed, Scopus, Web of Science, Google Scholar, and regional databases like African Journals Online (AJOL). We incorporated research from 2000 to 2025, focusing on human and animal myiasis in North African nations. Data extraction utilized a standardized template, focusing on assessing the quality of high-quality and reliable sources. The research revealed substantial discrepancies in myiasis management across urban and rural regions, and among several North African nations. Urban locations in Egypt, Tunisia, and Algeria had superior access to contemporary diagnostic instruments and therapies, while rural regions mainly depended on conventional remedies. Conflict-affected nations such as Libya and Sudan saw significant healthcare interruptions, heightening myiasis risks. Significant hurdles were restricted diagnostic instruments, erratic public health initiatives, and insufficient data from underreported regions like Mauritania and Western Sahara. Managing regional disparities in myiasis requires focused treatments, enhanced monitoring systems, and cooperation among governments, healthcare professionals, and communities. Future studies must emphasize cost-efficient solutions customized for local circumstances, especially in conflict-affected and disadvantaged areas. By closing gaps in knowledge and practice, we may facilitate more fair and effective management of myiasis across North Africa and beyond.